The limits of doubt : the moral and political implications of skepticism - Lom, Petr, 1968- (Albany : State University of New York Press, 2001)
"The Limits of Doubt studies the skepticism of Nietzsche, Sextus Empiricus, Hobbes, Diderot, and Montaigne in order to illustrate how different forms of skepticism can produce remarkably different implications. These include toleration; chastening of character; the prohibition of cruelty; indifference; corrosiveness of liberal principles; and freeing of the will from moral restraint. Demonstrating how skepticism is an under-determined and unstable category, accompanied by varying unquestioned intentions and beliefs, this book shows how these limits of doubt shape its various possible implications. A unique examination of skepticism from a moral and political perspective. The Limits of Doubt will interest all those concerned with the possibilities for life in an age of doubt."--Jacket
1 Skepticism and the Politics of Domination 11 -- 2 Ancient Skepticism: Happiness Above Truth 31 -- 3 Hobbes and the Peace of Dogmatic Skepticism 47 -- 4 Denis Diderot and Doubt: Constructive Skepticism 59 -- 5 Skepticism, Cruelty, Custom, and Toleration: Michel de Montaigne 75.
Includes bibliographical references (pages 119-133) and index.
Print version record.
JSTOR
Keywords: Skepticism -- Moral and ethical aspects; Skepticism -- Political aspects; Ethics; Ethics; Scepticisme -- Aspect moral; Scepticisme -- Aspect politique; Morale; ethics (philosophy); PHILOSOPHY -- Movements -- Rationalism; Skepticism -- Moral and ethical aspects; Skepticism -- Political aspects